Development and Characterization of an Electroless Plated Silver/Cysteine Sensor Platform for the Electrochemical Determination of Aflatoxin B1 - Wacoo, Alex Paul; Ocheng, Mathew; Wendiro, Deborah; California Vuzi, Peter; Hawumba, Joseph F. (Journal of Sensors, 2016)
An electroless plated silver/cysteine sensor platform [Glass|silver|cysteine|aflatoxin B1|horseradish peroxidase] for the Electrochemical detection of aflatoxin B1 was developed and characterized. This involved four major steps: (1) an electroless deposition of silver (plating) onto a glass slide, (2) immobilization of cysteine; (3) conjugation of aflatoxin B1 to cysteine groups; and (4) blocking of free cysteine groups with horseradish peroxidase (HRP).The binding of cysteine to the silver was demonstrated by the disappearance of thiol (S-H) groups at 2500 cm−1 using Fourier transmittance infrared spectra (FT-IR), while the subsequent steps in the assembly of sensor platform were monitored using both FT-IR and cyclic voltammetry, respectively. The sensor platform exhibited a broadened nonsymmetrical redox couple as indicated by cyclic voltammetry. The platform was further characterized for sensitivity and limit of detection. The indirect competitive immunoassay format, whereby free and immobilized aflatoxin B1 on the sensor competed for the binding site of free anti-aflatoxin B1 antibody, was used at various concentrations of aflatoxin B1. The sensor generated differential staircase voltammogram that was inversely proportional to the concentration of aflatoxin B1 and aflatoxin B1 in the range of 0.06–1.1 ng/mL with a detection limit of 0.08 ng/mL could be detected.
Keywords: Electroless Plated Silver/Cysteine; Sensor Platform; Electrochemical Determination; Aflatoxin B1